THE INFLUENCE OF PRODUCT QUALITY, LIFESTYLE, AND INFLUENCER MARKETING ON IMPULSE BUYING OF SKINTIFIC PRODUCTS AT THE TIKTOK SHOP AMONG GENERATION Z - Virginia Pandiangan; Willem J. F. A. Tumbuan; Regina T. Saerang (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
With the evolution of social media into shopping platform for more intense, convenient, and innovative business-customer interactions, the phenomenon of impulse buying has become widespread. This study focused on TikTok Shop, a flourishing social platform, particularly popular among Generation Z who are closely connected to smartphones and social media. The beauty brand, Skintific, widely acclaimed on various platforms, has achieved significant sales on TikTok Shop. This study used the statistical method SPSS 29 to analyze the influence of product quality, lifestyle, and influencer marketing on impulse buying of Skintific products at the TikTok Shop among Generation Z. The research method applied is quantitative, using an online questionnaire targeted at Generation Z TikTok Shop users across Indonesia. Purposive sampling with certain criteria was used to select a sample of 104 respondents. The analysis results indicate that product quality has no influence on impulse buying, meanwhile lifestyle and influencer marketing have a positive influence on impulse buying. Simultaneously, product quality, lifestyle, and influencer marketing have a positive influence on impulse buying.   Keywords: Product Quality, Lifestyle, Influencer Marketing, Impulse Buying